DOI: 10.31274/etd-180810-345
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-magnesium antagonism in high magnesium vineyard soils

Abstract: The Iowa wine and grape industry underwent a rapid phase of growth at the turn of the 21 st century that is continuing to evolve and develop today. Cultivar trials across the state found that 'Marquette' grapevines were performing poorly in eastern Iowa while other cultivars performed well. A preliminary investigation suggested a magnesium induced potassium deficiency and/or above optimum soil pH as the cause of poor growth of 'Marquette'. Soils in the upper Mississippi Valley are derived from limestone and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
0
16
0
4
Order By: Relevance
“…Such K uptake restriction may happen when soils have high magnesium concentration relative to K concentration. The Mg-induced K deficiency in crops is well documented and can occur in soils with an available K/Mg concentration below 0.32 [47]. A recent assessment of K + /(Ca 2+ + Mg 2+ ) ratios in soils from two similar locations nearby our experimental sites indicated values less than 0.17 [46].…”
Section: Discussionmentioning
confidence: 62%
“…Such K uptake restriction may happen when soils have high magnesium concentration relative to K concentration. The Mg-induced K deficiency in crops is well documented and can occur in soils with an available K/Mg concentration below 0.32 [47]. A recent assessment of K + /(Ca 2+ + Mg 2+ ) ratios in soils from two similar locations nearby our experimental sites indicated values less than 0.17 [46].…”
Section: Discussionmentioning
confidence: 62%
“…High Mg 2+ in soils creates big blocks that are hard to be broken down and thus reduces K and N efficiency (Genever, 2010). Moreover, Mg induced K deficiency (Hannan, 2011).On the other hand, Dontsova and Norton (2001) observed that availability of K and ammonium can also be affected by a soil's preference for Ca 2+ . They suggested further study is needed to explore how distribution of K between solution, exchangeable and non-exchangeable phases is influenced by the Ca/Mg ratio.…”
Section: )mentioning
confidence: 99%
“…In the control (unbalanced soil), the soil Ca/K, Mg/K, and Ca/Mg ratios were too wide, indicating high contents of Ca and Mg in the soil that could easily displace K from the soil exchange complex inducing a low uptake of K in a phenomenon referred to as 'competitive ion effect'. It is reported that a high magnesium and calcium content could induce a competitive ion effect in which K is less absorbed by plants [10,21]. However, this imbalance in soil exchangeable cations could be successfully mitigated with additional K from fertilizers and biochar that contain a high amount of K, as observed in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, the cation ratio of Ca/K and Mg/K significantly increased, leading to a relatively higher ratio of both Mg/K and Ca/K in the sesame leaf tissues, thus suggesting low content of K in the plant. Furthermore, Hannan [10] reported that an excess of Mg could cause a K deficiency in grapevine plants at a ratio of K/Mg < 0.30 in soil. These studies suggested that care should be taken while supplying a high amount of Ca and Mg in soil in order to avoid ionic imbalances in plants.…”
Section: Introductionmentioning
confidence: 99%